Endoleaks: current concepts and treatments - Zia Ur Rehman (Journal of the Pakistan Medical Association, 2021)
Endoleaks are the most common complications following endovascular aneurysm repair. Depending upon their origin, there are five types of endoleaks, types I-V, which can also be classified as direct and indirect endoleaks. Direct endoleaks type 1 and III have higher risk of aneurysm rupture due to rapid sac expansion, and require immediate correction. Indirect endoleaks types II, IV and V have a relatively benign course compared to direct endoleaks. Most of them resolve with time and very few of them need interventions upon sac enlargement. Type V endotension is a special situation where there is sac enlargement despite no demonstrable endoleak. Proper planning and appropriate selection of stent-graft can prevent most of these endoleaks. With improvement in stent-graft technology, the incidence of endoleaks has been reduced. The current narrative review was planned to describe the pathophysiology, risk factors and treatment options for each type of endoleak. Continuous...